MENTAL WELL-BEING OF SPORTING WOMEN - Terentyev, A.E.; Vodyakha, S.A.; Vodyakha, Y.E.; Aristov, L.S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to test benefits of habitual physical training and sporting lifestyles for the 25-42 year-old women’s mental health and wellness. Methods and structure of the study. We randomly sampled for the study the 25-42 year-old (32.7 years on average, SD =.51) women (n=78) residing in Yekaterinburg with representative variations in ages, education levels and socio-economic situations. The sample was tested in February through April 2019. We split the sample into an unsporting Reference Group (RG, n= 38) and habitually sporting/ physical education and sports-devoted Experimental Group (EG, n= 48). Results and conclusion. The test and survey data analyzed herein give us good grounds to believe that physical progress is associated with mental well-being progress – in agreement with the prior study findings. The sporting versus unsporting women’s group mental well-being / mental health test differences showed the habitual physical training and sports being mostly beneficial for the following: individual self-control and self-management mechanisms; stress tolerance; independence; and self-esteem. On the whole, the study demonstrated benefits of habitual physical training and sporting lifestyles for the 25-42 year-old women’s mental health and well-being.